Enhancing lecturers' productivity through AI in Universitas Slamet Riyadi, Surakarta - Lukas Maserona Sarungu; Riska Wirawan; Agung Yudhistira Nugroho (Universitas Muhammadiyah Magelang, 2024)
One of the challenges in enhancing the productivity of FISIP UNISRI lecturers is the suboptimal utilization of Artificial Intelligence (AI) to support their work, along with inefficient implementation of AI. This service has dual objectives: introducing AI to those unfamiliar with it and providing education on crafting effective prompts to ensure AI-generated responses meet expectations. To achieve these goals, the method involves delivering focused material on AI introduction and prompt creation effectiveness. Results from this program indicate that all 8 lecturers who had not used AI before are now proficient and frequently utilize AI (100%). Additionally, among the 10 lecturers with prior AI experience, 8 individuals (80%) reported the training's benefits in enhancing prompt creation effectiveness, leading to more elaborate and expectation-aligned AI outputs.